Strengthened competition in payment services - Markus Demary; Christian Rusche (Institut der deutschen Wirtschaft (IW), 2018)
Starting on January 13, 2018, the Second Payment Services Directive (PSD2) will apply in the European Union. Among other things, the Directive's aim is to adapt regulation to the innovations in payment services and to promote the Single Market for non-cash payments. However, PSD2 will only strengthen competition between payment services under a common standard for the access to banking accounts.
Keywords: 330